Appropriation/Expropriation : Recent work from the Halifax community (Halifax : Mount Saint Vincent University Art Gallery, 1983)
Adams, Rose ; Bean, Bob ; Campbell, Bruce ; Eyland, Cliff ; Geller, Wendy ; Gourlay, Sheena ; Kennedy, Garry ; Kibbins, Gary ; Koenig, Ingrid ; McEachern, Susan ; Needham, Wilma ; Slopek, Edward : Quinn, Cathy ; Lounder, Barbara
Appropriation/Expropriation Recent work from the Halifax community, Mount Saint Vincent University Art Gallery, Halifax, 11 March - 3 April 1983
boek